2019
DOI: 10.1007/s11270-019-4170-5
|View full text |Cite
|
Sign up to set email alerts
|

Removal of High Concentrations Decachlorobiphenyl of Earthworm Eisenia fetida and its Symbiotic Bacteria in a Vermicomposting System

Abstract: Persistent organic pollutants (POPs) such as polychlorinated biphenyls (PCBs) are a group of high-risk synthetic substances for human and environmental health. Currently, the study of sites contaminated by the spillage of equipment PCBs containing have been considered targeted areas for the study of bacterial communities with potential for PCBs degradation. There in isolation of bacterial strains is vital for use in biodegradable processes, such as bacterial bioaugmentation, which accelerates the development o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Likewise, no discernable differences between the different samples were determined in related to electrical conductivity (EC). It is known that the EC is related to the salinity content of the soil (Zenteno-Rojas et al 2019 ). The samples obtained in soil F had the highest EC value (0.076 dS m −1 ), this could be due to the high content of Ca 2+ and Mg 2+ ions that is common in soils obtained from tropical forests (regosols).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, no discernable differences between the different samples were determined in related to electrical conductivity (EC). It is known that the EC is related to the salinity content of the soil (Zenteno-Rojas et al 2019 ). The samples obtained in soil F had the highest EC value (0.076 dS m −1 ), this could be due to the high content of Ca 2+ and Mg 2+ ions that is common in soils obtained from tropical forests (regosols).…”
Section: Discussionmentioning
confidence: 99%
“…The soil characteristics were determined in all of the evaluated treatments at the end of the bioaugmentation process (day 21) to analyze the changes produced between the treatments. The pH and electric conductivity (EC) were measured by using a digital pH meter, a Mettler Toledo ® (Columbus, OH, USA) Model S220 (New York, NY, USA), in a 1:10 (weight/volume) aqueous solution [15]. The soil organic matter (SOM) content, total carbon, and C:N ratio were analyzed according to AOAC methods [19].…”
Section: Physicochemical Characterization Of Bioaugmented Soilmentioning
confidence: 99%
“…In the same way, in previous works, we have contributed to the study of highly efficient alternatives for the elimination and degradation of PCBs in contaminated soils. We examined vermicomposting systems and symbiotic bacteria from the earthworm Eisenia fetida and found that large amounts of PCB-209 could be removed [15]. Likewise, rhizospheric and endophytic bacteria associated with the Ocimun basilicum plant had the ability to remove up to 500 mg/L of PCB-209 [16].…”
Section: Introductionmentioning
confidence: 99%
“…A. schindleri can be found in different environments and is seldomly used for biodegradation of pesticides. Some studies indicate that A. schindleri can biodegrade different chemicals such as polyhydroxyalkanoates (Boyandin et al 2012), organic pollutants decachlorobiphenyl (Zenteno-Rojas et al 2019) and acetate (Sigala et al 2017). The aim of this study is to biodegrade α-endosulfan and α-cypermethrin using A. schindleri B7 isolated from insect ora and to determine their degradation products.…”
Section: Introductionmentioning
confidence: 99%